Strategic Management for Organizational Performance: from Which Come the Mistakes of Strategic Decision-Making - Imane, Ahdil; Driss, Harrizi (European Journal of Economics and Business Studies, 2017)
The current context of organizations is marked by changes or even dramatic changes. The main function of decision-makers becomes increasingly difficult and complex. At the same time, performance has become one of the most important topics within companies. That is why management and economics have addressed this central issue. Faced with a turbulent environment characterized by rough and fierce competition, guaranteeing performance and above all maintaining it becomes a strategic priority, which is why strategic management will be called upon. So our article will deal first with the performance of companies and the role of strategic management in this sought-after performance; and the precautions to be taken into account in strategic decision-making. To do this, we will begin our research by the conceptual framework of performance, to justify the contribution of strategic management in the performance of the company. The paper will conclude with an analysis of strategic decision-making and recommendations. The methodology used in this paper is a literature review.